Popular culture and the 'crisis of masculinity' - Jennifer Lemon (Communicare)
The eighties and nineties have wit nessed a renewed and unpre cedented Interest in men and mas culinity due to the emergence of the alleged contemporary 'crisis of masculinity'. This has been most preva lent in popular culture representations, which appear on the sur face to offer the modern man a whole range of 'new' roles and rela tionships, freeing him from patria chal entrapment and the dicates and demands of the traditional male sex role. The New Man Is Imaged as soft, sensitive, expressive and un afraid to show his emotions. New erotosized Images have made their appearance, and men are Imaged as sex objects in a way that only women were represented In the past. However, the question arises as to what these Images mean, and whether or not they represent any change In the patriarchal status quo In Western societies. In this article an attempt is made to deconstruct some of the new notions of masculinity in the light of the contempo rary 'crisis of masculinity', and the new popular culture representations of men In the mass media.